Strategic management across enterprise functions: an international competiveness pespective - Zapata, Luis Fernando Bustamante; Pérez, Isabel Amalia Porto; Taboada, Fernando Hernández (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Internationalization is a real chance of growth, or at least an important survival strategy in a globalized, highly competitive and changing market. This document describes strategic management across enterprise functions- technical, commercial, financial, accounting, security and management- as a required action for international competitiveness. We followed the analytical method listing he demands of a globalized market that transform every enterprise area. Then we propose some of the possible applicable strategies for each of pressure in order to acquire international competitiveness. Based on theoretical references, it is established that strategic management across enterprise functions eases organizational internationalization. It is necessary to further debate on applicable strategies from a managerial perspective.